(untitled) (Bulletin KNOB, 1997)
Following the example of architect H.P. Berlage, the Amsterdam architect Jan de Bie Leuveling Tjeenk (1885-1940) visited the United States of America in 1912, as part of a world tour. Provided with letters of recommendation from amongst others Berlage, the architect J.A. van Straaten and the Ministry of Foreign Affairs, Tjeenk was given the opportunity to get in touch with his colleagues on the other side of the world. He found the required written information on the architectural climate in America in articles in e.g. Bouwkundig Weekblad Architectura (Architectural Weekly). On June 3 1912 Tjeenk arrived in the New York harbour by the vessel ’De Nieuw Amsterdam’. At a breathtaking speed Tjeenk visited a lot of modern buildings in this city and got in touch with several architects. During his journey from the East to the West coast he saw and studied various well-known buildings, such as The Guaranty Building of Louis Sullivan and the administrative building of The Larkin Factories of Frank Lloyd Wright, as well as less-known ones. The personal encounter with Sullivan in Chicago made a great impression on the young architect and he regarded this as one of the high points of his journey. Through a coincidence a visit to Wright only just failed to take place, but Tjeenk did meet Wright’s most talented pupils, such as Richard E. Schmidt, Walter Burley Griffin, Marion Mahoney and Dwight Heald Perkins. It was particularly in the work of this group of architects, now known under the coordinating name of ’The Prairie School’ or ’The Chicago School of Architecture’ that Tjeenk recognized the modern spirit of the new American architecture. The influence these architects had on Tjeenk is to be traced in the design of the architect’s own house of 1925. During his journey through the United States Tjeenk kept a diary, which as yet has never been published. The diary contains a lot of valuable Information on the American world of building and on the various prominent architects in the first quarter of this century. Although the journey was made at a relatively early stage in the Dutch-American interaction and in spite of the similarity in style between some of Tjeenk’s buildings and the creations of the Prairie School, this architect and his work have never been discussed within the framework of ’Americana’ before.